GIS TECHNOLOGY BASED AGRICULTURAL INFORMATION MANAGEMENT SYSTEM - Patchaiappan, Patchaiappan; G. Rengamani, G. Rengamani (International Journal of Supply Chain Management, 2018)
Improving agricultural capability is an issue for made countries as well as rather for the entire world including rising economies, and it is seen that engaging more vital adequacy will fortify the necessity for more significant use of information development on the residence. The agrarian information organization system uses GIS advancement to utilize and give bound together organization of estate information about things like things, producers, yields, and quality. The association between advancement records and parameters, for instance, thing yield and quality can be shown.